Research on energy-saving and emissions reduction efficiency in Chinese thermal power companies. Issue 5 (August 2020) - Xu, Yue; Wang, Zebin; Chiu, Yung-Ho; Ren, Fangrong
In a low-carbon economic environment, China's thermal power industry has developed at a rapid speed. Faced with significant development bottlenecks, however, promoting energy conservation and technological innovation has become the current goals of the country's thermal power industry. Taking into account the heterogeneity of production technology, we utilize panel data of 23 listed thermal power companies in the Shanghai and Shenzhen stock markets from 2010 to 2015 as samples and divide them into large, medium, and small groups according to company size. Based on a meta-frontier function and the non-radial data envelopment analysis method, we evaluate the performance of energy-saving and emissions reduction in the thermal power industry when considering slack variables of energy input and undesirable output. The empirical study's results show that the mean energy-saving and emissions reduction performance in this power industry is generally low and exhibits significant differences under different frontiers. The performance of energy-saving and emissions reduction from high to low is small, large, and medium-size groups. The small-size group seems to obtain the industry-leading level production technology. Moreover, the technology gap and insufficient management are the primary sources of the total performance loss.